2009
DOI: 10.1177/1420326x08101945
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Volatile Organic Compounds in Atopy Patients' Houses in South Korea

Abstract: This study was undertaken to determine the concentrations of volatile organic compounds (VOCs) in the indoor air of atopy patients' (atopic dermatitis 50, allergic asthma 36) and control houses (28 nonpatients). A goal of this study was also to investigate whether indoor VOCs were risk factors for the development of atopic sensitization. Eleven alkanes, 13 aromatics, 7 chlorinated hydrocarbons, 3 terpenes, and 15 aldehyds were measured from 10 March to 15 June, 2006. Aldehyde compounds are the most abundant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This review has found many publications that associate concentrations below those used as reference for toluene, ethylbenzene and xylenes with illnesses classified as critical by the EPA-IRIS, including processes such as the increase in oxidative stress [39] that are precursor mechanisms of chronic diseases, such as cancer, and illnesses related to chronic inflammation, such as bronchitis [46], asthma [47] and atopy [48].…”
Section: Discussionmentioning
confidence: 99%
“…This review has found many publications that associate concentrations below those used as reference for toluene, ethylbenzene and xylenes with illnesses classified as critical by the EPA-IRIS, including processes such as the increase in oxidative stress [39] that are precursor mechanisms of chronic diseases, such as cancer, and illnesses related to chronic inflammation, such as bronchitis [46], asthma [47] and atopy [48].…”
Section: Discussionmentioning
confidence: 99%
“…The Korean threshold for formaldehyde in indoor air as specified for an 8 h value is 100 μg/m 3 , which is higher than the recommended threshold of other countries [18]. A previous study reported that the concentration of VOCs in the indoor air of houses of patients with AD and allergic asthma was approximately 1.4–2.0 fold higher than in the houses of the same age group without atopy [7]. In our study, the concentrations of TVOCs were found to be higher than values in previous studies on eco-friendly materials or in the houses of patients with AD [19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the indoor environment is of particular interest with regard to its role in the development and aggravation of allergic diseases because young children spend most of their time indoors [3,4]. Many studies have reported the relationship between indoor air pollutants and asthma [5,6], but fewer have reported the effects of indoor air pollutants on AD, a common and troublesome condition among young children [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2012) studied at urban areas of Korea; it revealed that among the VOCs, aromatic VOCs had shown a significant contribution with 74% followed by other VOCs like halogenated paraffin, halogenated olefin, and halogenated aromatic VOCs. Choi et al (2009) revealed that the area-specific trends of VOC concentration were to be industrial > commercial > residential, in these areas; toluene and xylene have been shown to be remarkably high from measured VOCs (BTEX). Hajizadeh et al (2018) studied at Yazd (Iran) between 2015 and 2016; the average BTEX concentration was found to be 114 ± 119 µg m −3 ; among them, toluene (38 ± 42 µg m −3 ) and xylene (41 ± 45 µg m −3 ) have shown the highest concentrations; it might have been originated from industrial activities.…”
Section: Comparison Of Btex Level In India With Other Asian Countriesmentioning
confidence: 99%